2015
DOI: 10.1007/s11626-015-9908-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low molecular weight hyaluronan combined with carprofen on canine osteoarthritis articular chondrocytes and cartilage explants in vitro

Abstract: Intra-articular injection with non-steroidal anti-inflammatory drugs (NSAIDs) is used to treat inflammatory joint disease, but the side effects of NSAIDs include chondrotoxicity. Hyaluronan has shown positive effects on chondrocytes by reducing apoptosis and increasing proteoglycan synthesis. The purposes of this study were to evaluate the effects of low molecular weight hyaluronan (low MW HA), carprofen 25 mg/ml, carprofen 12.5 mg/ml, and a combination of HA and carprofen on canine osteoarthritis (OA) articul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…However, in this study, it was found that the combination treatment with CAR with HA (Comb24 and Comb48) did not decrease chondrotoxicity (and did not increase chondrocyte viability). Similar to our previous study involving OA chondrocyte cultures, co-treatment with HA did not decrease chondrotoxicity caused by CAR (Euppayo et al, 2015), triamcinolone acetonide (Euppayo et al, 2016), dexamethasone (Siengdee et al, 2015) and prednisolone (Siengdee et al, 2015). However, some studies have shown that HA could reduce cytotoxicity on chondrocyte viability after cells were exposed to bupivacaine (Onur, Sitron & Dang, 2013), indomethacin (Hashizume & Mihara, 2009), dexamethasone (Hashizume & Mihara, 2009) and celecoxib (Hashizume & Mihara, 2009).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…However, in this study, it was found that the combination treatment with CAR with HA (Comb24 and Comb48) did not decrease chondrotoxicity (and did not increase chondrocyte viability). Similar to our previous study involving OA chondrocyte cultures, co-treatment with HA did not decrease chondrotoxicity caused by CAR (Euppayo et al, 2015), triamcinolone acetonide (Euppayo et al, 2016), dexamethasone (Siengdee et al, 2015) and prednisolone (Siengdee et al, 2015). However, some studies have shown that HA could reduce cytotoxicity on chondrocyte viability after cells were exposed to bupivacaine (Onur, Sitron & Dang, 2013), indomethacin (Hashizume & Mihara, 2009), dexamethasone (Hashizume & Mihara, 2009) and celecoxib (Hashizume & Mihara, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…However, HA could lessen the side effects of fluoroquinolones when treatment was given in conjunction with those other drugs (Siengdee et al, 2016). On the contrary, the therapeutic effects of HA could not mitigate the side effects of carprofen (Euppayo et al, 2015), corticosteroid (Siengdee et al, 2015) and triamcinolone acetonide (Euppayo et al, 2016) when subjects were treated with HA at the same time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, treatment with HA can activate normal chondrocytes to increase the expression of ACAN , which is a key matrix molecule of cartilage, concomitant with upregulation of inhibitors of the matrix‐destructive enzyme TIMP1 and downregulation of MMP3 , a critical matrix‐degrading enzyme. This evidence suggests that HA has a protective effect on primary canine chondrocytes, similar to other reports (Julovi et al ., ; Peng et al ., ; Euppayo et al ., ). Co‐treatment with HA and Enro was successful in increasing s‐GAG production, which may reflect new matrix synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Part III, in vitro studies — There were five studies [ 22 , 23 , 38 40 ], including anabolic gene ( ACAN and COL2A1 ) expression, catabolic gene ( ADAMTS5 , COX-2 , IL-1β , MMP2 , MMP3 , and MMP13 ) expression, and GAG remaining in chondrocyte pellets or cartilage explants.…”
Section: Resultsmentioning
confidence: 99%